Analysis of the Effect of HVAC System Modification towards Indoor Air Quality (IAQ) and Microbiological Growth at Accommodation and Office Buildings in an Oil and Gas Industry - Sabrina Valentina; Sjahrul Meizar Nasri; Rani Herespatiagni (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Indoor Air Quality (IAQ) problems, such as high relative humidity and microbiological (bacteria and mold) growth in accommodation and office buildings, can cause health effects for the occupants. People commonly have activities inside the buildings all day long. This study aimed to determine the impact of HVAC systems on IAQ parameters and microbiological growth. The study was conducted in accommodation and office buildings that had been identified with IAQ problems. The research methodology used a quantitative cross-sectional study design with statistical comparison analysis and statistical correlation analysis. The statistic results showed that relative humidity (RH) significantly had a strong correlation (r=0.520, 95% CI) with mold growth in ambient air of accommodation; O2 had a significantly strong correlation (r=0.541, 95% CI) with bacteria growth in ambient air at the office; VOC (r=0.853, 95% CI) and CO2 (r=0.803, 95% CI) had a very strong correlation with mold growth at office surface area. High humidity contributed to risk on IAQ (OR=50, 95% CI). Significant improvement was shown in relative humidity at all buildings, especially at the office, but mold and bacteria growth were offered only at the accommodation. Therefore, a comprehensive evaluation was needed to improve the IAQ and modify the HVAC system.